Pendampingan secara Daring untuk Peningkatan Kapabilitas Pelaku Usaha Mikro dan Performa Usaha - Rebecca, Yemima Tanya; Nathalia, Kintania; Harsono, Elizabeth Christy; Widjaja, Steven; Nurkholis, Ilham; Djauhari, Jason; Gerrald, Greg; Suhartanto, Eko (Journal Pemberdayaan Masyarakat Indonesia, 2023)
The increase in the number of micro, small and medium enterprises (MSMEs) has had a positive effect on the Indonesian economy. However, the pandemic has suppressed MSME activities in various regions in Indonesia, including MSMEs in Kuningan Regency, one of which is the Family Fried Chicken (FFC) micro business. This article discusses operational, marketing and financial strategies that can be implemented to assist FFC business owners in developing their business. The preparation of these strategies was carried out by the owner of the FFC and a group of third year Prasetiya Mulya University students. In implementing these strategies, students provide assistance for four months online. For students, this activity is part of the Community Development course, which is a four credit course.